The Security Jawbreaker. - Vachon, Phil (Communications of the ACM, 2024)
The article discusses the evolution of enterprise security in parallel with household security, emphasizing the transition from perimeter defenses to comprehensive access controls amid the internet's ubiquity. It explores the challenges of maintaining security as businesses expose more applications externally and advocates for segmented access based on roles and responsibilities to prevent breaches. Finally, it underscores the importance of pervasive authority checks within systems to minimize vulnerabilities and ensure robust security.